A Brain-Penetrating Hsp90 Inhibitor NXD30001 Inhibits Glioblastoma as a Monotherapy or in Combination With Radiation - Chen, Hao; Gong, Yuanying; Ma, Yufang; Thompson, Reid C.; Wang, Jialiang; Cheng, Zhixiang; Xue, Lixia (Frontiers in Pharmacology, 2020)
Glioblastoma multiforme (GBM) is a highly heterogeneous disease, which is initiated and sustained by various molecular alterations in an array of signal transduction pathways. Heat-shock protein 90 (Hsp90) is a molecular chaperone and is critically implicated in folding and activation of a diverse group of client proteins, many of which are key regulators for glioblastoma biology. We here assessed the anti-neoplastic efficacy of a novel brain-penetrating Hsp90 inhibitor NXD30001 as a monotherapy and combined with radiation in vitro and in vivo. Our results demonstrated that NXD30001 potently inhibited neurosphere formation, growth and survival of CD133+ GBM cells with the half maximal inhibitory concentration at low nanomolar range, but CD133- GBM cells were less sensitive to NXD30001. NXD30001 also increased radio-sensitivity in glioblastoma stem cells (GSCs) at suboptimal concentrations. Moreover, NXD30001 dose-dependently decreased phosphorylation levels of multiple Hsp90 client proteins which play key roles in GBM, such as EGFR, Akt, c-Myc and Notch1. In addition, NXD30001 could impair DNA damage response and endoplasmic reticulum stress response after radiotherapy by alteration of the related proteins expression. In a murine orthotopic model of human glioblastoma, NXD30001 marvelously induced tumor regression and extended median survival of tumor-bearing mice by approximately 20% when compared with the vehicle group (37 days vs 31 days, P<0.05). Radiotherapy solely increased median survival of tumor-bearing mice from 31 days to 38 days (P<0.05), while NXD30001 combined with radiation further extended survival to 43 days (P<0.05). We concluded that GSCs are more sensitive to NXD30001 than non-stem GBM cells, and NXD30001 in combination with radiation exerts better inhibitive effect in GBM progression than monotherapy.